RAW STARCH-DEGRADING AMYLASE FROM BACTERIA IN KARANG MUMUS RIVER, SAMARINDA - Astuti, Winni; Adawiyah, Rabiatul; Putri, Amanda Aulia; Pratiwi, Djihan Ryn (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2024)
Raw starch-degrading amylase (RSDA) is an enzyme that has the ability to degrade starch granules into glucose without undergoing gelatinization. This research was conducted to explore and characterize extracellular RSDA-producing bacteria from body water of the Karang Mumus River, Samarinda. RSDA activity was analyzed qualitatively in nutrient agar containing 1% starch granules, bacterial colonies with RSDA activity are clear halos around bacterial colonies after the plates were flooded with iodine solution. Five of the 14 bacterial colonies secreted an RSDA extracellularly. The RSDA enzyme from the 5 bacteria was tested for amylase activity using the Dinitrosalicylic Acid (DNS) method. Bacteria with colony code KM 5 had the highest RSDA activity of 0.332 U/mL.The optimum working conditions for RSDA are at pH 5 and a temperature of 40Â°C. Identification of bacterial genotypes using the 16S rRNA gene showed that KM5 was Klebsiella sp, referred to as Klebsiella KM5.